2020
DOI: 10.32890/jict2020.19.3.2
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Model From Multidimensional Layering: Personal Finance Information Framework Using Mobile Software Interface Operations

Abstract: End user involvement is crucial in improving software development processes. Hence, nowadays user interface (UI) and user experience (UX) are particularly concerned with end user interactions in many software designs as most methodologies have inconsistencies between design and implementation. Besides, it is relatively difficult to make changes in complex software and personal finance application is one of the more complex software to design, develop, and adapt. This paper proposes the development of a mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The architecture design of the vermiculture smart farming kit is premeditated following the layered proposal and the architecture design for precision agriculture. The software composition divided into layers has claimed to support in many researches [7], [24], [26]. Elijah, Rahman, Orikumhi, Leow, and Hindia have cited that IoT technology consists of a multilayer architecture and devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture design of the vermiculture smart farming kit is premeditated following the layered proposal and the architecture design for precision agriculture. The software composition divided into layers has claimed to support in many researches [7], [24], [26]. Elijah, Rahman, Orikumhi, Leow, and Hindia have cited that IoT technology consists of a multilayer architecture and devices.…”
Section: Discussionmentioning
confidence: 99%
“…Farmer responsibilities are concerned as a domain solution to coordinate the smart devices and to adapt the new transformation. For example, the daily farming operations such as irrigation and atmospheric monitoring, fertilization management such as verifying good materials and manuring [6], and financial management [7] such as cost calculation and expense records. The farm clarifications are studied in various areas such as soil stages, environmental conditions, plants, and animals.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, numerous dimensions present a financial statement's balance. These dimensions are combined to execute and compute a component's process (Rukhiran & Netinant, 2020). Xiaodong et al (1998) proposed a two-dimensional model for software development that incorporates both object-oriented and formal methods.…”
Section: Three-dimensional Layeringmentioning
confidence: 99%
“…Based on personal financial information, a framework (Rukhiran & Netinant, 2020) is divided into three layers to support database tables, informative operations, and programming. Financial statements are classified into three categories: income, expense, and liability.…”
Section: Introductionmentioning
confidence: 99%
“…Eames et al believe that details can contribute to the improvement of usability and the experience of pleasant emotions 2 . Therefore, the interface should include the evaluation of pleasure and attraction of the interface 13 . Most studies focus on the evaluation of usability, while some have confirmed the impact of microinteraction user senses.…”
Section: Introductionmentioning
confidence: 99%